TAX CHALLENGES OF THE DIGITAL ECONOMY - E. L. Gulkova; M. V. Karp; M. V. Tipalina (Вестник университета)
The issues of changing the tax system of the Russian Federation, the system of tax control under the influence of digital technologies have been examined. Electronic government services in the field of taxation, as well as the prospects and directions for the further development and expansion of electronic services used for taxpayers and tax authorities have been considered. The problems of taxation of operations with cryptocurrencies and their tax regulation have been touched upon. Conclusions have been formulated to improve the efficiency of taxation and tax control in the transition to a digital economy.